مابعد جدیدیت میں مغربی فکر و تہذیب پر ابن رشد کے اثراتInfluence of Averroes on Western Civilization and its thought in Postmodernism (Al-Qamar, 2023)
This article deals with the influence of Averroes on Western Civilization and its thought in Postmodernism. Averroes' influence on Leo Strauss' post-modern historiography is most prominent in this period. Averroes' ideas were well received when International Organizations took over the right to interpret the Western concept of Human Rights and Human Equality. Averroes study helps to remedy the conflict of civilizations. Averroes' influence is evident in the Zionist state, a Western representative in the East. Averroes' country later became a bigoted Christian country. Now a days, thinking changed there, a university was established in the name of him and research on his ideas became common in Spain and all over the world. Universities and organizations are being built in his name in the East and the West. A comprehensive study of Averroes is underway in western universities, the most notable of which is the encyclopedic type compilation of Fawat Sizgin about him. In postmodernism, Averroes' Orientalistic study has increased, and in the growing wave of blasphemy of Prophethood in the West, Ayatollah Khomeini and Salman Rushdie are considered symbols of both sides. Rushdie's claim of his relationship with Averroes is imaginary, because Averroes and the Iranian Spiritual leader are more closed in their thoughts.
Keywords: Averroes; Fawat Sizgin; Postmodernism; Orientalist; Blasphemy of Prophethood; Khomeini; Western Civilization; Leo Strauss; Human Rights; Zionist